Influence of plasticizer structure on stability of polystyrene scintillators optical characteristics - Senchishin, V.G.; Borisenko, A.Yu.; Titskaja, V.D.; Koba, V.S.; Lebedev, V.N.; Adadurov, A.F.; Osadchenko, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
The radiation and thermal stability of optical characteristics of polystyrene scintillators modified by plasticizers based on derivatives of naphthalene, ditolylmethylene, diphenylene oxide, ether of phthalic acid and oligo-phenyl-methyl-siloxanes were studied. It was shown that structure and size of plasticizer molecule make a definite influence on scintillators characteristics of operational conditions stability.